Enhancing Employee Engagement and Employee Loyalty among Generation Y Employees : A Case Study of Large Hotels in Hatyai, Songkhla - Sorawit Wutijaroenwong (Prince of Songkla University, 2020)
Thesis (M.B.A., Business Administration (International Program))--Prince of Songkla University, 2017